Commissural misalignment independently predicts leaflet thrombosis after transcatheter aortic valve implantation - Jung, Susanne; Ammon, Fabian; Smolka, Silvia; Moshage, Maximilian; Marwan, Mohamed; Achenbach, Stephan (Clinical Research in Cardiology, 2023)
Aims: Transcatheter aortic valve implantation (TAVI) has become a minimally invasive alternative to surgical aortic valve replacement. Hypo-attenuated leaflet thickening (HALT)—a marker of subclinical leaflet thrombosis commonly detected by cardiac computed tomography (CT) after TAVI—may influence valve durability and function. The purpose of this study was to compare commissural alignment of the native and prosthetic aortic valves in cardiac CT in subjects with and without HALT and thereby identify commissural misalignment as potential predictor for leaflet thrombosis after TAVI. Methods and results: In 170 subjects, 85 with and 85 without HALT in post-TAVI CT, commissural orientation of the prosthesis was determined comparing native and prosthetic aortic valve orientation in cardiac CT by measuring the commissural angle relative to the right coronary ostium in the aortic valve plane. For the prosthetic valve, any deviation ≤ 15° compared to the native valve was classified as “aligned”; 16–30° as “mild”, 31–45° as “moderate” and ≥ 45° as “severe” misalignment. Among subjects with HALT, median angular deviation was higher (36°, IQR 31°) than in the control group (29°, IQR 29°, p = 0.042). “Severe” misalignment was more frequent in subjects who developed HALT (n = 31, 37%) compared to the control group (n = 17, 20%, p = 0.013). In logistic regression analysis, more severe deviation (p = 0.015, OR = 1.02 per 1° deviation) and “severe” misalignment (p = 0.018, OR = 2.2) represented independent predictors for the occurrence of HALT after TAVI. Conclusion: Subclinical leaflet thrombosis after TAVI is associated with commissural misalignment. Potential clinical advantages of obtaining commissural alignment remain to be systematically assessed. Graphical abstract: [Figure not available: see fulltext.] Association of HALT with commissural misalignment after TAVI. HALT hypo-attenuated leaflet thickening, IQR interquartile range, TAVI transfemoral aortic valve replacement
CRIS-Team Scopus Importer:2023-04-21
Keywords: Commissural misalignment; HALT; Leaflet thrombosis; TAVI